Fixing a match or two: Cricket, public confession and moral regeneration - Wardrop, Joan (The Australian Anthropological Society Inc, 2002)
‘In a moment of stupidity and weakness I allowed Satan and the world to dictate terms to me. The moment I took my eyes off Jesus my whole world turned dark.’ With these words, the former South African cricket captain, Hansie Cronje, publicly confessed that he had been a cheat, attempted to make peace with the United Cricket Board, located his fall from grace within a peculiarly fundamentalist Christian frame of guilt and atonement, and subtly connected himself and his corruption with a set of understandings about the simultaneous rigidity and vulnerability of the moral order that have grown over the past two centuries to inform, underpin and idealise Afrikaner collective notions of self. That moral order and its vulnerabilities, I will suggest here, have framed a collective identity and a collective sense of both victimhood and entitlement, within which any act becomes acceptable and possible if it can be deemed necessary.